Uma interpretação psicogenética da moda - Guedes, Regina Rosari Mugayar (1984)
The objective of this work is to study the corporal image instituted by the culture and especifically by the fashion, in particular, along the genesis of its variants, in order to reach the psyco-anthropologic invariant axies, that constitute the logic-generative large categories, which build its permanent subjacent structure. It's wanted to settle the relationship between the psychologic system defined by the body as an entity that transcends the biological level and the interpersonal comunication system. The fashion emerges in the interconnection between the body and social comunication, where the corporal reality constitutes a basis for the social and psychological signs. For that, the system of language changes has been extended and verbal and non-verbal, considerating the corporal image as a modality of the latter. Using the structuralist method, it's tried to transfer the concepts from Saussure's Linguistics to the corporal image, synchoronous and diachronously configured. It has been established, either, the respective principal invariant category, composed by a bipolar axie: the identity and the diferentiation, semanticly supplied with afetive and cultural factors.